Analysis of Seismic Hazards and Vulnerability throughout Indonesia Based on 1999-2003 Earthquake Data Using the Microseismic Method - muthia puteri amarda; - Syafriani (Department of Physics – Universitas Negeri Padang UNP, 2021)
Indonesia is an archipelagic country that has a complex geological structure. Its location at the confluence of three plates, namely the Eurasian plate, the Indo-Australian plate, and the Pacific plate causes high tectonic activity. This seismic activity causes high seismicity levels, especially along the subduction zone. An earthquake with a large magnitude can occur and cause a high level of damage, so it is necessary to know about the language of earthquake resistance. Earthquake vulnerability is useful for mitigating earthquakes that will occur so that people are more alert to earthquake disasters that can occur anytime and anywhere. This research is a descriptive type of research, namely by collecting data on the JINSET (Japan Indonesian Seismic Network) earthquake catalog in 1999-2003 with M greater than 5 S.R. Earthquake hazard data processing using geopsy software for HVSR analysis. The horizontal component data is divided by the vertical component in the frequency domain so that the H/V value is obtained.